1957
DOI: 10.1677/joe.0.0150180
|View full text |Cite
|
Sign up to set email alerts
|

The Excretion of Pregnanediol and Adrenocortical Activity

Abstract: A new method of assay was applied to the determination of pregnanediol in urines from patients in whom the presence of a placenta or a corpus luteum could be excluded. The normal variation of pregnanediol content in such urines was examined. It was shown that operative stress or the intravenous administration of corticotrophin caused an increased output of pregnanediol. Quantitatively significant amounts of urinary pregnanediol could not be detected after adrenalectomy nor did adrenalectomized patients respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1958
1958
1976
1976

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The methods first evolved for the assay of urinary pregnanediol were lacking in sensitivity. This view is supported by the recent investigations of Klopper, Strong and Cook (1957) who showed that, when ovarian pregnanediol could be excluded, the urinary levels of pregnanediol reflected the activity of the adrenal glands. The original studies showed that pregnanediol was a metabolite of progesterone.…”
mentioning
confidence: 72%
“…The methods first evolved for the assay of urinary pregnanediol were lacking in sensitivity. This view is supported by the recent investigations of Klopper, Strong and Cook (1957) who showed that, when ovarian pregnanediol could be excluded, the urinary levels of pregnanediol reflected the activity of the adrenal glands. The original studies showed that pregnanediol was a metabolite of progesterone.…”
mentioning
confidence: 72%
“…There is a characteristic rise in urinary pregnanediol excretion during the ovulatory menstrual cycle, although the extent to which this occurs is rather variable and the difference between levels in the follicular and luteal phase may not be very striking. That this rise is due to extra adrenal precursors was demonstrated by a study after bilateral adrenalectomy (Klopper, Strong and Cook, 1957). If pregnanediol assays are to be used instead of plasma progesterone assays then it is probable that the main field of application is in studying the effect of therapy-notably the induction of ovulation.…”
Section: F Sommervillementioning
confidence: 99%
“…On th e o th e r h a n d we do n o t know w hy it is n o rm ally p ro d u ced b y th e a d re n a ls in m ales to such an e x te n t th a t th e levels o f " a d re n a l" p reg n an d io l range from 0.38 to 1.42 mg p er 24 hours [44], w hich is alm o st th e sam e level as in p o st m eno p au sal w om en [45] or w hy A CTH p ro duced a four-fold increase in u rin a ry p re g n a n d io l ex cretio n , w hich fell to a v ery low level a fte r b ila te ra l ad re n a le cto in v . T he w eak an d u n c e rta in a c tiv ity o f p ro g esterone on u te rin e can cer [47] seem s to be d u e n o t to its h o rm onal b u t m ore to a c y to s ta tic p ro p e rty [48] as show n by its a c tiv ity on H eL a a n d K B -cells in v itro [49].…”
Section: Com Parison O F Different S Tra In S O F M Ice (4 X F D M Imentioning
confidence: 99%